2020
DOI: 10.1021/acs.joc.0c00745
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Reaction of Phosphines, Benzynes, and CO2: Facile Synthesis of Stable Zwitterionic Phosphonium Inner Salts

Abstract: The first synthesis of benzyne-derived stable zwitterions is reported. Benzynes generated in situ from 2-(trimethylsilyl)­aryl triflates undergo a multicomponent reaction with phosphines and CO2 to produce the stable 1,5-zwitterionic species in moderate to excellent isolated yields, which provides a novel method for the preparation of phosphonium inner salts under mild and transition-metal-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 55 publications
(31 reference statements)
0
8
0
1
Order By: Relevance
“…Subsequently, they demonstrated that different kinds of acyclic and cyclic activated carbonyl compounds 8- 123 could participate in the same kind of transformation through a formal [3 + 2] cycloaddition fashion, leading to the formation of substituted (spiro)­benzoxaphosphole derivatives 8-124 in moderate to high yields (Scheme b) . Recently, the groups of Biju and Cai/He independently employed CO 2 as the third component and prepared zwitterionic phosphonium benzoates 8-125 (Scheme c). No annulated benzooxaphosphol-3­(1 H )-ones were formed in this reaction system.…”
Section: Multicomponent Reactions (Mcrs)mentioning
confidence: 99%
“…Subsequently, they demonstrated that different kinds of acyclic and cyclic activated carbonyl compounds 8- 123 could participate in the same kind of transformation through a formal [3 + 2] cycloaddition fashion, leading to the formation of substituted (spiro)­benzoxaphosphole derivatives 8-124 in moderate to high yields (Scheme b) . Recently, the groups of Biju and Cai/He independently employed CO 2 as the third component and prepared zwitterionic phosphonium benzoates 8-125 (Scheme c). No annulated benzooxaphosphol-3­(1 H )-ones were formed in this reaction system.…”
Section: Multicomponent Reactions (Mcrs)mentioning
confidence: 99%
“…Based on the above experimental results and previous reports, ,, a plausible main reaction pathway for the formation of 4a is outlined in Scheme . Benzyne, which is generated by fluoride-induced elimination of benzyne precursor 1a , suffers a nucleophilic attack of triethyl phosphite to produce the 1,3-zwitterionic intermediate 8 , which is trapped by CCl 4 to form the intermediate 9 .…”
mentioning
confidence: 54%
“…Arynes including benzyne have been of particular interest due to their high reactivity and broad applications in organic synthesis. , Notably, aryne chemistry has been widely utilized in constructing aryl C–P bonds under mild reaction conditions, providing various arylphosphorus compounds with good efficiency . Three-component reactions involving arynes, which mainly include the initial addition of nucleophiles to arynes and subsequent trapping of the aryl anion intermediate with electrophiles, enable the rapid assembly of 1,2-disubstituted arenes with ample structural diversification. , However, three-component reactions of arynes, phosphorus nucleophiles, and other electrophiles have received less attention, and the employment of phosphorus nucleophiles and the electrophilic components is limited to tertiary phosphines and carbonyl compounds . It is noteworthy that Wittig and co-workers have reported a series of work on the ortho -difunctionalization reaction of arynes and organophosphorus compounds .…”
mentioning
confidence: 99%
“…The product structure was confirmed by single crystal X‐ray analysis, and the distance between carboxyl oxygen and the phosphorus atom showed no sign of P−O bonds in solid states. Almost at the same time, Cai, He and co‐workers reported the similar synthetic protocol between arynes, phosphines and CO 2 [16] . Aside from the above‐mentioned mechanism, the authors proposed another possible pathway based on control experiment results.…”
Section: Reactions Of Aryne With Organophosphorus(iii) Compoundsmentioning
confidence: 88%